Effect of verification imaging on in vivo dosimetry results using Gafchromic EBT3 film. Issue 11 (November 2016) - Aland, Trent; Moylan, Rebecca; Kairn, Tanya; Trapp, Jamie
Highlights: Gafchromic EBT3 film is affected by dose received from CBCT and kV planar imaging during in vivo dosimetry. Imaging dose will appear on in vivo measurements as an apparent treatment dose. Where kV planar imaging is used, apparent treatment doses of up to 3.4 cGy were measured. For CBCT, apparent treatment doses ranged from 0.22 cGy up to 3.78 cGy. Apparent treatment dose from imaging must be accounted for during in vivo dosimetry. Abstract: In this work, the apparent treatment dose that kV planar or CBCT imaging contributes to Gafchromic EBT3 film used for in vivo dosimetry, was investigated. Gafchromic EBT3 film pieces were attached to a variety of phantoms and irradiated using the linear accelerator's built-in kV imaging system, in both kV planar mode and CBCT mode. To evaluate the sensitivity of the film in the clinical scenario where dose contributions are received from both imaging and treatment, additional pieces of film were irradiated using base doses of 50 cGy and then irradiated using selected kV planar and CBCT techniques. For kV planar imaging, apparent treatment doses of up to 3.4 cGy per image pair were seen. For CBCT, apparent treatment doses ranged from 0.22 cGy to 3.78 cGy. These apparent doses were reproducible with and without the inclusion of the 50 cGy base dose. The contribution of apparent treatment dose from both planar kV as well as CBCT imaging can be detected, even in conjunction with an actual treatment dose. The magnitude of the apparent dose was found to be dependent on patient geometry, scanning protocol, and measurement location. It was found that the apparent treatment dose from the imaging could add up to 8% of additional uncertainty to the in vivo dosimetry result, if not taken into account. It is possible for this apparent treatment dose to be accounted for by subtraction of the experimentally determined apparent doses from in vivo measurements, as demonstrated in this work.